Blockchain as an update to the islamic education ecosystem: analysis and adoption framework - Suyuti, Imam; Prihantoro , Wahyu Kholis; Sumiati , Endang (At-Tajdid: Jurnal Ilmu Tarbiyah, 2024)
This research comprehensively explores the potential of blockchain technology to revolutionize the Islamic education ecosystem, expanding the scope from merely improving transparency and data security to systematic reformers that support core Islamic values. Through an in-depth analytical approach, this study maps out how blockchain can improve accuracy, reliability, and efficiency in Islamic education administration, certification, and financial management. By applying a framework specifically designed to fulfill Shariah principles, the study offers new insights into ethical and effective technological solutions, promising substantial improvements in the way Islamic education is managed and delivered. Through case analysis and scenario modeling, the research also highlights implementation challenges, including cultural resistance and regulatory barriers, while offering strategies to overcome such issues. Finally, by focusing on the synergy between technological innovation and Islamic values, this research proposes blockchain not only as a technical tool but also as a medium to strengthen the identity and integrity of Islamic education.